Preference for Public Transportation Service Levels in Makassar City Towards Female Passenger Satisfaction - Annisya Alifvia Soehartono; Muhammad Daffa Musyary (PENA TEKNIK: Jurnal Ilmiah Ilmu-Ilmu Teknik, 2024)
Basic services are government affairs that are mandatory and entitled to be obtained by every citizen, one of which is public transportation services. Although it has been regulated by Minimum Service Standards (SPM), the quality of public transportation services in Makassar City is still low and has not met expectations and satisfaction, especially for female passengers. The purpose of this study was to determine the satisfaction of female passengers with the quality of public transportation services in Makassar City. The respondents of this study were 96 female passengers of public transportation in Makassar City. This research is descriptive qualitative study that refers to the Regulation of the Minister of Transportation of the Republic of Indonesia Number PM 29 of 2015. This regulation outlines criteria such as security, safety, comfort, affordability, equality, and regularity for assessing the quality of public transportation services in Makassar City. The data analysis technique in this study uses descriptive analysis employing the Community Satisfaction Indicator (SMI) analysis method. Based on the results of calculations using the public satisfaction index method, it is known that the total number of service elements has a score of 43.86. Although this indicates that the overall quality of service is quite good, it is considered that women are not satisfied with the service provided. The relationship between the level of satisfaction with the quality of service affects women's preferences in choosing the mode they want to use.